Analisa Quality of Services (QOS) Jaringan Komputer PLN Area Surakarta - Mubarok, Hari, Dr. Ir. Bana Handaga, M.Sc (2016)
Technical Services Division in each office Rayon under the control of PLN Area Surakarta worked for 24 hours to respond to the various customer complaints. The services using Aplikasi Pengaduan dan Keluhan Terpadu (APKT), Aplikasi Pelayanan Pelanggan Terpadu (AP2T), Aplikasi Pelayanan Pelanggan Terpadu Executive Information System (AP2T EIS), also Management Services, as well as management that is connected in realtime. The officer often complain about bad network connectivity on the application server so that the customer service to be not optimal. The monitoring, measuring, and evaluating were aplicated based on TIPHON standart for determine how the fluctuations and ability of computer network in Surakarta, especially on technical services. The monitoring is using Command Prompt approximatelly 24 hours. Aspects calculated are delay, jitter, throughput, and packetloss. From the measurements, delay value is under 150 ms and throughput value is below 3%. The main classical problems of network is atmospheric disturbance. According to the TIPHON standaritations, PLN Surakarta was very good.